Preservation Of Peaceful Culture Through The Panther Scout Program At Giritirto 2 State Primary School To Reduce Bullying - Putri Hadinata, Andrefi Salsabilla; Wahdan Najib Habiby (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Bullying is a social phenomenon that still occurs frequently at elementary school level. Bullying behavior can be carried out individually or in groups. The negative impact of bullying in the school environment for victims is decreased learning achievement and self-isolation. The absence of special interventions from schools to reduce bullying behavior among students is the background for this research. The aim of this research is to determine the effectiveness of the Panther Scout program by preserving a culture of peace-loving to reduce cases of bullying. The research method is quantitative with an experimental design. Before data analysis was carried out, a one-way validity and reliability test was carried out on 28 respondents with an rtable of 0.374 on the research instrument. Data collection techniques use observation, interviews, documentation, and filling out questionnaires by respondents. The findings in this research are that there are students who combine verbal and relational bullying behavior simultaneously. The implication of the Panther Scout program is a reduction in cases of bullying at elementary school level, both verbal, physical and relational bullying.